Analysis of Sustainable Development Progress in the State of Sabah, Malaysia - Huda, Mohd Ikbal Mohd; Ridzuan, Abdul Rahim; Ridzuan, Mohd Ikhram Mohd; Madan, Marfunizah (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Development is a process of creating a prosperous society in terms of its economic, social, political and environmental quality. The government plays a crucial role in realising sustainable development by transforming the state and district economies and balancing socioeconomic income. Issues on Sabah’s development have long been debated. The extent of the interest among relevant parties regarding Sabah’s development and how the government ‘tolerates’ ensuring that Sabah is developing at the same pace as other states must be examined crucially. This research aims to investigate the condition of Sabah based on three main pillars of sustainable development: economics, social and environment. The studies only adapted descriptive analysis geared by a questionnaire distributed only to the local Sabahan. Overall, we received 30 respondents, and the outcomes are mixed. Overall, the majority of Sabahan is satisfied with the growth achieved by Sabah; however, they feel pressured by the cost of living and agree that there are still huge poverty issues in this state. Meanwhile, in environmental quality, the local Sabahan are satisfied with the government's approach to maintaining the environment despite huge development in major cities such as Kota Kinabalu. These studies could give meaningful insight to the policymakers in ensuring the development of Sabah is according to the United Nation’s sustainable development policy.